Effect of Early Mobilization on Intestine Peristaltic in Post Laparatomy Surgery in Inpatient Room - Noor, Mohammad Arifin; Rusli, Rusli; Dunggio, Abdul Rivai Saleh; Aditia, Donny; Horhoruw, Andrias; Achmad, Viyan Septiyana; Febrianti, Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Mobilization is an independent action for a nurse in carrying out nursing care for post-surgical patients. Many benefits can be achieved from early postoperative mobilization exercises, including increasing the speed of breathing depth, increasing circulation, increasing urination and metabolism. Laparotomy is an action involving the abdominal cavity that can be performed with open surgery. This research aims a. maintain body functions and prevent deterioration and restore the range of motion of certain activities so that sufferers can return to normal or at least be able to meet their daily needs. b. Streamlining blood circulation. c. helps breathing to become strong for and to determine the effect of early mobilization on intestinal peristalsis in postoperative laparotomy patients in the Inpatient Room of the Nene Mallomo Regional General Hospital. The research design used in this study was a quasi-experimental design: non-equivalent control group design. This research was carried out by providing intervention in the form of giving early mobilization. While the control group was not given any treatment by the researchers apart from observing intestinal peristalsis. Sampling was carried out by purposive sampling method with a total sample of 30 people consisting of a control group and a treatment group of 15 people each, then the results were tested by means of the Independent Sample T-Test with a significance level of α = 0.05. The results of this study found that changes in intestinal peristalsis in postoperative laparotomy patients in the Inpatient Room of the Nene Mallomo Regional General Hospital in the group given early mobilization (treatment group) averaged 11.200 (±0.262), changes in intestinal peristalsis in postoperative laparotomy patients in the Inpatient Room of the Nene Mallomo Regional General Hospital in the control group the average was 1.533 (± 0.723), and there was an effect of early mobilization on changes in intestinal peristalsis in postoperative laparotomy patients in the Inpatient Room of the Nene Mallomo Regional General Hospital (p=0.001 ). The conclusion is that early mobilization can increase intestinal peristalsis in post-laparotomy patients in the Inpatient Room of the Nene Mallomo Regional General Hospital so that it is expected that health workers will continue to carry out early mobilization in post-laparotomy patients and in post-laparotomy patients as early as possible to speed up the recovery process. function of the patient's digestive system.